Analysis of Students' Mathematical Problem Solving Ability in The Topic of Matrix - Kholipah, Nuzuliah; Prabawanto, Sufyani (International Conference on Elementary Education, 2020)
Mathematical problem-solving ability is one of the important abilities for students that should be achieved. However, some studies show that students are still have difficulty in solving mathematical non-routine problem, especially in the topic of matrix. The deficiency of students' ability can be caused by some sources, such as the text book that be used by students or the teacher and the students’ prior learning experiences. Students have difficulty not only in solving the problem but also in understanding the problems, especially in the problems that deal with word problem or real world problem. Therefore, learning that integrates knowledge, skills, and creative thinking and emphasizes more on the experience and active involvement of students in solving problems. This study aims to analyze how students solve mathematical non-routine tasks, espicially in the topic of matrix. The method used in this study was descriptive qualitative. The subjects in this study were 5 students of XI graders of a Vocational High School in Bandung. Data collection techniques used in this study were observation, test, and interview. Based on data analysis, the result of the study shows that students have difficulty in making formula that will be applied in solving the problems.